Nefroprotective Effect of Gynura procumbens Extract Against Paracetamol Toxicity in Rats - Ishak, Pertiwi; Kabo, Peter; Yusrini Djabir, Yulia (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
ABSTRACT Excessive doses of paracetamol have the potential to cause acute kidney injury and even death. Gynura procumbens has been traditionally used as folk-medicine for kidney disease. This study aimed to examine the nephroprotective effect of Gynura procumbens leaf extract against paracetamol-induced nephrotoxicity in rats. Twenty-five male wistar rats (150-200 g) were divided into 5 groups. Healthy control group, placebo group, and 3 extract treatment groups that received either 100 mg/kg, 200 mg/kg or 300 mg/kg dose. The placebo (sodium carboxymethyl cellulose) or extract was given 4 consecutive days prior to paracetamol (2400 mg/kg) administration on day 5. Blood samples were withdrawn before treatment initiated (day 0), after treatment before paracetamol administration (day 5) and 24-hour after paracetamol administration (day 6). Blood samples were analyzed to obtain urea and creatinine levels. In addition, histopathological analysis was performed on the renal tissue. Paracetamol administration was shown to significantly increase the urea and creatinine levels, and the extract at 300 mg/kg dose was able to significantly prevent the elevation of the renal biomarkers. The histopathological analysis also revealed a significant reduction in renal histopathological injury in 300 mg/kg extract group. It can be concluded that the ethanolic extract of the Gynura procumbens at a dose of 300 mg/kg has a good protective effect on kidney function and tissue structure. Key words: Gynura procumbens, nephroprotective, paracetamol